Dakwah Filosofis KH Imam Mubasyir Malo - Indah Dwi Syayekti, Ela (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2023)
da'wah is important to maintain the morale of the nation through the messages conveyed. The message conveyed can be expressed explicitly by quoting verses of the Koran or implicitly by explaining the philosophical value of a matter. One of the preachers who uses philosophical values ​​for something is KH Imam Mubasyir. The purpose of this research is to find out how to preach KH Imam Mubasyir so that he is close to the community. This study used a qualitative approach with observation and documentation methods. The data used are KH Imam Mubasyir's lectures which were observed directly or using video. The results of this study indicate that the priest's tradition is redundant in preaching using surrounding objects, themes and conditions at the place of recitation to convey the message of da'wah to the community philosophically. This philosophical meaning is adapted to the understanding of mad'u, who on average work as farmers. This research contributes to the development of message packaging and da'wah methods. Apart from that practically, it is hoped that the da'i will get other alternatives in carrying out his da'wah methods.